Wildflowers and Ferns of Red River Gorge and the Greater Red River Basin - Dourson, Dan; Dourson, Judy (Book collections on Project MUSE., 2019)
The Red River Gorge's intricate canyon system features an abundance of high sandstone cliffs, rock shelters, waterfalls, and natural bridges, making it one of the world's top rock-climbing destinations. The Gorge, known for its unspoiled scenic beauty and numerous hiking trails, is one of Kentucky's most popular natural destinations, attracting over 500,000 visitors a year. While books about hiking, climbing, and other recreational activities in the area are readily available, Wildflowers and Ferns of Red River Gorge is the first book specifically devoted to the biodiversity of the Gorge and its watershed. Authors Dan and Judy Dourson introduce the geology and cultural history of the gorge but focus on the incredible diversity of both common and rare flora of this unique ecosystem. With over 1,000 color images and numerous illustrations covering over 1,500 species currently known to exist in the watershed, Wildflowers and Ferns of Red River Gorge is designed to be accessible to the casual hiker and of use to the seasoned naturalist. Rare and endangered species are highlighted as well as a few other important, but often ignored, non-flowering plant groups, including green algae, fungi, slime molds, lichens, and mosses. In addition, a small section on flowering woody vines, shrubs, and trees is included, making the book the most comprehensive natural guide to one of Kentucky's most well-known natural recreational areas.